2022
DOI: 10.1200/jco.21.02372
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Late Mortality and Life Expectancy After Autologous Blood or Marrow Transplantation Over Three Decades: A BMTSS Report

Abstract: PURPOSE We determined trends in life expectancy and cause-specific late mortality after autologous blood or marrow transplantation (BMT) performed over a 30-year period, using the BMT Survivor Study. METHODS We constructed a cohort of 4,702 individuals with hematologic neoplasms who lived ≥ 2 years after autologous BMT performed between 1981 and 2014 at three transplant centers. The end of follow-up was April 19, 2021. The primary exposure variable was autologous BMT performed in four eras: 1981-1999; 2000-200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
(48 reference statements)
0
15
0
Order By: Relevance
“…The causes of morbidity and mortality associated with CH mirror the common causes of non‐relapse mortality generally seen after ASCT. Indeed, in a recent retrospective study of over 4700 patients who survived for at least 2 years after ASCT, the most common causes of non‐relapse mortality were infections, secondary malignancies, cardiovascular, and renal disease 40 . Consequently, the life expectancy of transplant recipients was reduced by seven years compared to the general population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The causes of morbidity and mortality associated with CH mirror the common causes of non‐relapse mortality generally seen after ASCT. Indeed, in a recent retrospective study of over 4700 patients who survived for at least 2 years after ASCT, the most common causes of non‐relapse mortality were infections, secondary malignancies, cardiovascular, and renal disease 40 . Consequently, the life expectancy of transplant recipients was reduced by seven years compared to the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in a recent retrospective study of over 4700 patients who survived for at least 2 years after ASCT, the most common causes of non-relapse mortality were infections, secondary malignancies, cardiovascular, and renal disease. 40 Consequently, the life expectancy of transplant recipients was reduced by seven years compared to the general population. The authors found that the all-cause mortality improved in the modern eras, whereas no such improvement was observed for patients with non-Hodgkin lympho.…”
Section: Impact Of Ch On Osmentioning
confidence: 99%
“…While there has been a consistent trend of improvement in the survival following both autologous and allogeneic hematopoietic cell transplantation bone marrow transplant therapies decade over decade (47,48), cardiovascular toxicities (49) continue to be frequent complications, along with infections and graft vs. host disease. This has resulted in evolving practice guidelines targeting preventive evaluations pretransplant, monitoring peri-transplant, and surveillance in long term survivors (50,51).…”
Section: Cardiovascular Complications Of Cellular Imunotherapiesmentioning
confidence: 99%
“…In the article that accompanies this editorial, 1 the authors representing the Bone Marrow Transplant Survivor Study have extended previous work evaluating outcomes in more than 4,000 patients of all ages (median age, 53 years; range, 0-78 years) surviving for at least 2 years after an autograft for hematologic malignancies in four eras spanning 1981-2014. This timely study provides valuable information when counseling autograft patients about long-term nonrelapse outcomes.…”
mentioning
confidence: 99%
“…In the article that accompanies this editorial, the authors 1 representing the Bone Marrow Transplant Survivor Study (a collaboration between City of Hope and the University of Minnesota and, more recently, the University of Alabama) have extended their previous work in children 2 by including 4,702 patients of all ages (median age, 53 years; range, 0-78 years) after an autograft for hematologic malignancies in four eras: 1981-1999; 2000-2005; 2006-2010; and 2011-2014 (Fig 1). 1 The study focuses on outcomes in patients surviving at least 2 years, and comparison across the eras was restricted to 5 years of follow-up to ensure adequate follow-up from the most current era. Unsurprising observations include the reduction in the use of total-body irradiation (TBI) in conditioning (56% to 5%), and the switch from a mixture of marrow and peripheral blood stem cells (PBPCs) as the source of reconstitution originally to almost 100% PBPCs since 2000.…”
mentioning
confidence: 99%